2006
DOI: 10.1111/j.1463-1318.2006.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Strictureplasty vs resection in small bowel Crohn's disease: an evaluation of short‐term outcomes and recurrence

Abstract: Patients with small bowel CD undergoing strictureplasty alone may have fewer postoperative complications than those undergoing a concomitant bowel resection. However, surgical recurrence maybe higher following strictureplasty alone than with a concomitant small bowel resection. Patients may require appropriate preoperative counselling regarding the pros and cons of each operative technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 51 publications
1
27
0
3
Order By: Relevance
“…Warunkiem bezpiecznego poszerzenia endoskopowego jest brak owrzodzeń oraz krótki odcinek zwężenia (do 4 cm). Alternatywną metodą jest chirurgiczna plastyka zwężeń [101,102] (zwłaszcza u chorych zagrożonych zespołem krótkiego jelita, ze zwężeniami krótszymi niż 10 cm), a w przypadku długiego odcinka lub zwężeń wielopoziomowych oraz aktywnych zmian w zwężeniu -resekcja odcinkowa jelita [103]. Chirurgiczna plastyka zwężeń w jelicie grubym oraz wytworzenie zbiornika J-pouch nie są zalecane osób z ChLC.…”
Section: Le Ec Cz Ze En Ni Ie E C Ch Hi Ir Ru Ur Rg Gi Ic Cz Zn Ne Eunclassified
“…Warunkiem bezpiecznego poszerzenia endoskopowego jest brak owrzodzeń oraz krótki odcinek zwężenia (do 4 cm). Alternatywną metodą jest chirurgiczna plastyka zwężeń [101,102] (zwłaszcza u chorych zagrożonych zespołem krótkiego jelita, ze zwężeniami krótszymi niż 10 cm), a w przypadku długiego odcinka lub zwężeń wielopoziomowych oraz aktywnych zmian w zwężeniu -resekcja odcinkowa jelita [103]. Chirurgiczna plastyka zwężeń w jelicie grubym oraz wytworzenie zbiornika J-pouch nie są zalecane osób z ChLC.…”
Section: Le Ec Cz Ze En Ni Ie E C Ch Hi Ir Ru Ur Rg Gi Ic Cz Zn Ne Eunclassified
“…Stricturoplasty has also been associated with a risk of stricture relapse in 30-35 % of patients at 4-8 years [138,139]. Stricturoplasty is a safe alternative to resection in jejuno-ileal CD, including ileocolonic recurrence, with similar short-term and long-term results [140][141][142]. Reese et al [140] in their study revealed that there was an observed benefit of stricturoplasty over resection with regard to the overall early complications (17/134, 12.7 % in the stricturoplasty group and 36/188, 19.1 % in the resection group), but the difference was not statistically significant (p = 0.09).…”
Section: Stricturoplastymentioning
confidence: 95%
“…No significant difference is also reported in the recurrence rate after strictureplasty alone and strictureplasty plus resection. 16,20 However, metaanalysis of 7 studies performed by Reese et al 21 showed that patients who underwent resection had significantly longer recurrence-free survival than did those who underwent strictureplasty alone. In the present study, duration between previous operation and recurrence was significantly shorter in patients who underwent strictureplasty than in patients who underwent resection and anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists on the recurrence rate after strictureplasty and resection. 16,[18][19][20][21][22][23] Several invesigators 18,19 have reported no significant differences in rates of recurrence after strictureplasty versus resection. No significant difference is also reported in the recurrence rate after strictureplasty alone and strictureplasty plus resection.…”
Section: Discussionmentioning
confidence: 99%